Menulis Laporan Hasil Pengamatan Dengan Pendekatan Project Based Learning (Pjbl) Siswa Smp Negeri 11 Kota Tidore Kepulauan - Ismail, Julia; Sahmadan, Safrudin; Jailan, Putri Nurdiana; Muhammad, Yuliyanti; Muhammad, Ningsi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe the implementation of the project based learning model for writing observation reports at SMP Negeri 11 Tidore Islands City. The subjects of this research were teachers and students of class 8 at SMP Negeri 11 Tidore Islands City. The research object is the implementation of project based learning and material for writing observation reports. The research results show that the implementation of the project based learning model in learning can be achieved through activities; (1) Determining Fundamental Questions (Star With The Essential Question), (2) Designing a product plan, (3) Preparing a Project Implementation Schedule (Create a Schedule), (4) Monitoring project activity and development, (5) Testing project results, and (6) Evaluation of learning experiences. At the end of the activity, students produce a project in the form of a text report on the results of observations through the objects observed, so this research as a whole can be concluded that the application of project based learning in learning with the material of writing reports on observations can be said to be successful.